Are wider economic impacts of transport infrastructures always beneficial? Impacts of the Istanbul Metro on the generation of spatio-economic inequalities. (May 2015) - Beyazit, Eda
Highlights: Istanbul Metro accumulates capital in its surroundings and creates uneven geographies. The Metro has helped transformation from industry to CBD-related sectors in the area. Istanbul Metro is likely to drive off the low-skilled workforce from its surroundings. A thorough investigation of inequalities is needed in the analysis of WEIs. Ex-post evaluation of spatio-economic inequalities may improve analysis of WEIs. Abstract: Assessment of the Wider Economic Impacts (WEIs) of transport infrastructures has become crucial for justifying transport infrastructure investments, especially large-scale projects, not only for transport researchers but also for policy makers. Although the WEIs have been widely discussed in transport research and policy for more than a decade, these discussions lacked an important dimension: the likelihood of transport infrastructure investments to produce spatio-economic inequalities. This paper discusses the necessity of incorporating an understanding of spatio-economic inequalities in the analysis of WEIs. In order to do that, an ex-post analysis of the Istanbul Metro is carried out. In this sense, this paper also adds to the growing number of ex-post analysis of transport infrastructures. Through its findings based on the ex-post analysis of the impacts of the Istanbul Metro, this paper concludes that contemplating spatio-economic inequalities in ex-ante analysis of transport infrastructure investments will improve the calculation of WEIs of transport infrastructures. Such an approach is expected to help policy makers investing in projects that are less likely to produce spatio-economic inequalities.